Aplicação da inteligência artificial na gestão de projetos: aderência, impacto e grau de desenvolvimento - Pinkowski, Márcio Luiz (2023)
The developed project size, diversity, and complexity have increased over the time in our society. Thus, as a consequence of the continuous pursuit for success, Project Management (PM) knowledge and practices have evolved proportionally. In parallel, Artificial Intelligence (AI) technology has rapidly become present in our daily lives. From intelligent personal assistants to autonomous vehicles, Artificial Intelligence has evolved at an exponential pace for real-world applications. Considering the above scenario, this research aimed to find the potential use of Artificial Intelligence in Project Management from the perspectives of adherence, impact and degree of technological development, having as a central concern the challenges of this use, especially in a practical context. To achieve this goal, a Systematic Literature Review (SLR) and a Systematic Patents Review (SPR) on the theme were conducted. The first one focused on adherence and impact and the second on the determination of the Artificial Intelligence use development degree on Project Management. The measurement of results, in relation to practice and business vision, was carried out through multiple cases studies. The results point to the AI adherence to the PM and its increasing use in the various project management domains, as well as the number of patents registered for this purpose. Furthermore, it discusses the impacts on both project managers and organizations and measures the degree of AI development in GP through the use of the TRL (Technology Readiness Levels) concept. At the end, it concludes that AI has enormous potential to bring benefits to project management and, at the same time, has considerable challenges for its proper application.